Strategi Pemasaran Benih Padi Produksi PT. Sang Hyang Seri (persero) UBR III Desa Sereang Kecamatan Maritengngae Kabupaten Sidrap - Andi Iqbal; Irmayani Irmayani; Yusriadi Yusriadi (Universitas Muslim Maros, 2023)
This type of research is descriptive with a quantitative approach. Sources of data taken obtained from observations, interviews, and questionnaires using 15 respondents. This study uses SWOT analysis as a reference to determine the Strengths, Weaknesses, Opportunities and Threats that exist in the company PT Sang Hyang Seri (PERSERO) UBR III Sereang Village, Maritengae District, Sidrap Regency which consists of IFAS and EFAS Matrix, IE Matrix and SWOT Matrix.Based on the results of the research, it is known that PT. Sang Hyang Seri (PERSERO) UBR III Sidrap has produced research by analyzing the strengths, weaknesses, opportunities and threats that exist, so that this analysis leads to concerns that should be an opportunity or a strength. So that this research is highly recommended to be reviewed on the developments produced by the company. Looking at the results of research that occurs that there is a quality product that has a high score so that it becomes a reference that it is very feasible to be traded to consumers with a high selling value. Although there are several threats and weaknesses that exist, the opportunities are covered so that immediate action is taken for the sake of increasing this company such as expanding the area, promoting quality rice seeds, increasing employees and increasing the number of rice traders in the area in order to realize an increase in high consumer demand.